Pertactin contributes to shedding and transmission of Bordetella bronchiseptica. - Longhuan Ma (Public Library of Science (PLoS), 2021)
Whooping cough is resurging in the United States despite high vaccine coverage. The rapid rise of Bordetella pertussis isolates lacking pertactin (PRN), a key vaccine antigen, has led to concerns about vaccine-driven evolution. Previous studies showed that pertactin can mediate binding to mammalian cells in vitro and act as an immunomodulatory factor in resisting neutrophil-mediated clearance. To further investigate the role of PRN in vivo, we examined the functions of pertactin in the context of a more naturally low dose inoculation experimental system using C3H/HeJ mice that is more sensitive to effects on colonization, growth and spread within the respiratory tract, as well as an experimental approach to measure shedding and transmission between hosts. A B. bronchiseptica pertactin deletion mutant was found to behave similarly to its wild-type (WT) parental strain in colonization of the nasal cavity, trachea, and lungs of mice. However, the pertactin-deficient strain was shed from the nares of mice in much lower numbers, resulting in a significantly lower rate of transmission between hosts. Histological examination of respiratory epithelia revealed that pertactin-deficient bacteria induced substantially less inflammation and mucus accumulation than the WT strain and in vitro assays verified the effect of PRN on the induction of TNF-α by murine macrophages. Interestingly, only WT B. bronchiseptica could be recovered from the spleen of infected mice and were further observed to be intracellular among isolated splenocytes, indicating that pertactin contributes to systemic dissemination involving intracellular survival. These results suggest that pertactin can mediate interactions with immune cells and augments inflammation that contributes to bacterial shedding and transmission between hosts. Understanding the relative contributions of various factors to inflammation, mucus production, shedding and transmission will guide novel strategies to interfere with the reemergence of pertussis.